PENERAPAN SANKSI ADAT TERHADAP PERKARA KHALWAT DI TINGKAT GAMPONG (Studi Penelitian di Blang Pulo Kota Lhokseumawe) - Afriani, Maulida; Muhammad Nur, Muhammad Nur (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
A cultural approach that involves local wisdom and traditional institutions is a strategic and effective step in resolving crimes because society already has a legal system known as customary law. The use of customary law to resolve community cases is always carried out in the life of the Acehnese traditional community. The local wisdom of the people in Aceh in resolving disputes and disputes has now been confirmed in Qanun Number 9 of 2008 concerning the Development of Traditional Life and Customs. Islam strictly prohibits adultery, while Khalwat is a plot or opportunity for adultery to occur as well as an act that is contrary to existing customs. Violators of Islamic Sharia will receive strict warnings and customary sanctions/fines in accordance with established regulations. This research aims to explain how customary sanctions are resolved or applied to khalwat cases at the Gampong Blang Pulo level, Lhokseumawe City. This research uses empirical legal research, data collection is carried out through primary data and secondary data. Based on the results of the research, it was possible to resolve the khalwat case at the Traditional Court in Gampong Blang Pulo, Lhokseumawe City, namely to resolve it peacefully without violence against the perpetrator. During the trial process, the Gampong Customary Court first asked the residents, witnesses, the community and the perpetrator's statement about the chronology of the incident. Then the Gampong Customary Court deliberates to make a decision in accordance with the existing reusam or rules that have been established in the Gampong. The customary sanctions applied by the Gampong Customary Court so far are still in the form of warnings and warnings 1-2 times and the Gampong Customary Court provides guidance by summoning the perpetrator's parents and asking the perpetrator to promise not to do it again.